An investigation into the origin of the biased agonism associated with the urotensin II receptor activation2. (19th February 2015) - Brancaccio, Diego; Merlino, Francesco; Limatola, Antonio; Yousif, Ali Munaim; Gomez‐Monterrey, Isabel; Campiglia, Pietro; Novellino, Ettore; Grieco, Paolo; Carotenuto, Alfonso; Morelli, Giancarlo
<x xml:space="preserve">Abstract</x> The urotensin II receptor (UTR) has long been studied mainly for its involvement in the cardiovascular homeostasis both in health and disease state. Two endogenous ligands activate UTR, i.e. urotensin II (U‐II) and urotensin II‐related peptide (URP). Extensive expression of the two ligands uncovers the diversified pathophysiological effects mediated by the urotensinergic system such as cardiovascular disorders, smooth muscle cell proliferation, renal disease, diabetes, and tumour growth. As newly reported, U‐II and URP have distinct effects on transcriptional activity, cell proliferation, and myocardial contractile activities supporting the idea that U‐II and URP interact with UTR in a distinct manner (biased agonism). To shed light on the origin of the divergent activities of the two endogenous ligands, we performed a conformational study on URP by solution NMR in sodium dodecyl sulfate micelle solution and compared the obtained NMR structure of URP with that of hU‐II previously determined. Finally, we undertook docking studies between URP, hU‐II, and an UT receptor model. Copyright © 2015 European Peptide Society and John Wiley & Sons, Ltd.